High Prevalence of Precocious Puberty and Obesity in Childhood Narcolepsy with Cataplexy - Poli, Francesca (Associated Professional Sleep Societies, LLC, 2013)
STUDY OBJECTIVES: We analyzed the potential predictive factors for precocious puberty, observed in some cases of childhood narcolepsy with cataplexy (NC) and for obesity, a much more common feature of NC, through a systematic assessment of pubertal staging, body mass index (BMI), and metabolic/endocrine biochemical analyses. DESIGN: Cross-sectional on consecutive recruitment. SETTING: Hospital sleep center and pediatric unit. PATIENTS: Forty-three children and adolescents with NC versus 52 age-matched obese children as controls. INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: Patients underwent clinical interview, polysomnographic recordings, cerebrospinal fluid hypocretin-1 measurement, and human leukocyte antigen typing. Height, weight, arterial blood pressure, and Tanner pubertal stage were evaluated. Plasma lipid and glucose profiles were analyzed. When an altered pubertal development was clinically suspected, plasma concentrations of hypothalamic-pituitary-gonadal axis hormones were determined. Children with NC showed a high prevalence of overweight/obesity (74%) and a higher occurrence of precocious puberty (17%) than obese controls (1.9%). Isolated signs of accelerated pubertal development (thelarche, pubic hair, advanced bone age) were also present (41%). Precocious puberty was significantly predicted by a younger age at first NC symptom onset but not by overweight/obesity or other factors. In addition, overweight/obesity was predicted by younger age at diagnosis; additional predictors were found for overweight/obesity (short disease duration, younger age at weight gain and lower high-density lipoprotein cholesterol), which did not include precocious puberty. NC symptoms, pubertal signs appearance, and body weight gain developed in close temporal sequence. CONCLUSIONS: NC occurring during prepubertal age is frequently accompanied by precocious puberty and overweight/obesity, suggesting an extended hypothalamic dysfunction. The severity of these comorbidities and the potential related risks require a multidiagnostic approach and a tailored therapeutic management. CITATION: Poli F; Pizza F; Mignot E; Ferri R; Pagotto U; Taheri S; Finotti E; Bernardi F; Pirazzoli P; Cicognani A; Balsamo A; Nobili L; Bruni O; Plazzi G. High prevalence of precocious puberty and obesity in childhood narcolepsy with cataplexy. SLEEP 2013;36(2):175–181.